Figuratively speaking - Fogelin, Robert J. (New York ; Oxford : Oxford University Press, 2011)
In this updated edition of his brief, engaging book, Robert J. Fogelin examines figures of speech that concern meaning - irony hyperbole, understatement, similes, metaphors, and others - to show how they work and to explain their attraction.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Keywords: Figures of speech; Metaphor